Perception of cost-consciousness among medical students: an 11-item scale - Marilia Menezes Gusmao; Marta Silva Menezes; Carolina Villa Nova Aguiar; Liliane Lins; Ana Marice Ladeia; Luis Cláudio Correia (Escola Bahiana de Medicina e Saúde Pública, 2018)
Introduction: Managing healthcare resources in a cost-conscious way is an important topic in medical education.  A validated instrument to measure the perception of cost-conscious attitudes of medical students could be an important tool for university staff to understanding them and to plan and evaluate educational interventions to address them. Objectives: To validate a scale to measure the perception of cost-conscious attitudes among medical students. Method: Thirteen items from a survey to measure cost-conscious attitudes in medical students were used. Semantic validation and psychometric analysis (exploratory factor analysis, Cronbach alpha, and composite reliability test) were carried out. Results: A sample of 275 participants, of which 62% were female, with an average age of 25±3.1 years, completed the questionnaire. The best structure to measure the perceptions is the one-factor solution, with 11 of the 13 items remaining in the final version. Substantial Cronbach's alpha for this questionnaire was obtained 0.66 and composite reliability was 0.77. Conclusion: The results suggest that the questionnaire has a satisfactory psychometric quality and is therefore able to measure the perception of medical students about cost-conscious attitudes.